Attitudes to Learner Autonomy and Learning Strategies in Algerian EFL Context - NOUIOUA, Ramzi (Journal of Human Sciences, 2018)
Our research explored attitudes to learner autonomy, learning strategies, and language achievement among 82 Algerian EFL learners. Descriptive findings demonstrated learners' positive attitudes to learner autonomy and substantial use of strategies, with most preference for cognitive and metacognitive strategies and least preference for social strategies. Correlational analysis of attitudinal data showed significant relationships among perceptions of self-efficacy, self-initiated learning efforts, and learner’s agency with language achievement. Equally, metacognitive strategies and strategies for perseverant learning correlated significantly with learners’ achievement. One-way ANOVA showed significant differences in learners' attitudes and strategies across achievement, with high achievers showing significantly stronger positive perceptions of self-efficacy, attitudes to learner's role, perceptions of self-initiated learning, higher use of metacognitive strategies, and strategies for perseverant learning. Collectively, attitudes and strategies explained 39% of the variation in learners' achievement, with strategies for perseverant learning and social strategies as significant predictors. The research discusses the relevance of attitudes and learning strategies in language education research and the probable jeopardising effects of exam-orientated pedagogy within the educational system.